Fatigue crack paths and properties in A356-T6 aluminum alloy microstructurally modified by friction stir processing under different conditions - A. Tajiri; Y. Uematsu; T. Kakiuchi; Y. Suzuki (Fracture and Structural Integrity)
A356-T6 cast aluminum alloy is a light weight structural material, but fatigue crack initiates and propagates from a casting defect leading to final fracture. Thus it is important to eliminate casting defects. In this study, friction stir processing (FSP) was applied to A356-T6, in which rotating tool with probe and shoulder was plunged into the material and travels along the longitudinal direction to induce severe plastic deformation, resulting in the modification of microstructure. Two different processing conditions with low and high tool rotational speeds were tried and subsequently fully reversed fatigue tests were performed to investigate the effect of processing conditions on the crack initiation and propagation behavior. The fatigue strengths were successfully improved by both conditions due to the elimination of casting defects. But the lower tool rotational speed could further improve fatigue strength than the higher speed. EBSD analyses revealed that the higher tool rotational speed resulted in the severer texture having detrimental effects on fatigue crack initiation and propagation resistances.